The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/s20154138
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Characterization of the Human Knee Joint in Audible Frequencies

Abstract: Injuries and disorders affecting the knee joint are very common in athletes and older individuals. Passive and active vibration methods, such as acoustic emissions and modal analysis, are extensively used in both industry and the medical field to diagnose structural faults and disorders. To maximize the diagnostic potential of such vibration methods for knee injuries and disorders, a better understanding of the vibroacoustic characteristics of the knee must be developed. In this study, the linearity and vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Therefore, a representative analytical model should incorporate those effects to achieve a comparable analytical and experimental analysis. Moreover, it is worth mentioning that a previous study [53] on the vibration characterization of the human knee joint demonstrated a similar trend in the tibiofemoral vibration transmission of the human knee to the cadaver models, which is promising and partially mitigates concerns around potential translation from cadaver to human use.…”
Section: Comparison Of Model and Experimentsmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, a representative analytical model should incorporate those effects to achieve a comparable analytical and experimental analysis. Moreover, it is worth mentioning that a previous study [53] on the vibration characterization of the human knee joint demonstrated a similar trend in the tibiofemoral vibration transmission of the human knee to the cadaver models, which is promising and partially mitigates concerns around potential translation from cadaver to human use.…”
Section: Comparison Of Model and Experimentsmentioning
confidence: 61%
“…The shaker tip was pressed against the skin with an initial force level of 5 N to ensure that the shaker and sample stay in consistent contact throughout the tests. The compression force was selected based on an initial investigation of the comfortable threshold for the live subjects as reported in literature [53], and the maximum amplitude of the dynamic force exerted by the shaker during measurements. Two miniature, high sensitivity, and low mass accelerometers (Type 3225F, Dytran Instruments Inc., Chatsworth, CA) were placed on the medial and lateral aspects of the joint superior to the knee center.…”
Section: Vibration Test Setupmentioning
confidence: 99%
“…Thus, future studies could improve this model to more accurately represent the knee joint components and their biomechanical behavior. Furthermore, measurements of linearity and vibration transmissibility have been provided by Safaei et al [29] and could therefore provide useful data for such models.…”
Section: Discussionmentioning
confidence: 99%
“…As explained in the introduction, most previous studies have used either a microphone [10][11][12] or an accelerometer [2,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to measure VAG signals. The choice of an accelerometer depends on parameters such as its frequency response and its sensitivity.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Based on our previous clinical experience and on a thorough literature study—the vibroarthrography (VAG) can be successfully applied for evaluation of arthrokinematic motion quality [ 25 , 28 , 37 ], as the vibroacoustic emission level closely corresponds to the chondral deterioration degree [ 28 ]. In addition, the osteoarthritis (OA) affected knees produce vibroacoustic emissions with a greater frequency, higher peaks, and longer duration compared to the healthy ones [ 28 , 33 , 40 , 41 , 42 ]. In addition, the VAG signals can be helpful in the PFJ particular disorders differentiation, due to their specific disorder-related pattern character [ 25 , 28 , 33 , 37 ].…”
Section: Introductionmentioning
confidence: 99%